Vortices in theories with flat directions - Achúcarro,A; Davis,AC; Pickles,M; Urrestilla,J (Physical Review D Particles Fields Gravitation and Cosmology, 2002)
In theories with flat directions containing vortices, such as supersymmetric QED, there is a vacuum selection effect in the allowed asymptotic configurations. We explain the role played by gauge fields in this effect and give a simple criterion for determining what vacua will be chosen, namely, those that minimize the vector mass. We then consider the effect of vacuum selection on stable (Bogomol’nyi-Prasad-Sommerfield) non-topological vortices in a simple Abelian model with (Formula presented) supersymmetry which occurs as a low energy limit of Calabi-Yau compactifications of type II superstrings. In this case the magnetic flux spreads over an arbitrarily large area. We discuss the implications for cosmology and for superstring inspired magnetic confinement scenarios. © 2002 The American Physical Society.